Isolated extratesticular hematoma from intraoperative positioning during lumbar spinal surgery - Sunny Qi-Huang, MD (Radiology Case Reports, 2021)
Scrotal injury is present in less than 1% of all trauma-related injuries. Traumatic injuries of the scrotum are most commonly seen in penetrating or blunt injury but may also occur after iatrogenic causes such as in the intraoperative setting. We report a case of an isolated extratesticular hematoma incurred after scrotal trauma from prone intraoperative positioning during lumbar spinal surgery. Ultrasound performed following the procedure revealed an extratesticular hematoma without evidence of coexisting testicular injury. This case highlights an atypical insult to the scrotum and reinforces the need to ensure adequate positioning to prevent this postoperative complication.